Komunikasi Nonverbal dalam Pengembangan Desa Wisata Ramah Anak di Wong Rame - Suyani, Erni; Rahim, Rani; Sabri, Rijal; Asry, Wina (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study examines the pattern of nonverbal communication as an effort to fulfill children's basic rights through the concept of a child-friendly tourist village in the Wong Rame tourist area. This study uses a qualitative approach with a descriptive design that aims to gain an in-depth understanding of the phenomena that occur in the Wong Rame tourist attraction. The results of the study showed that the tourism concept applied combines natural beauty, resorts and restaurants supported by the provision of play areas to support visitor comfort. Nonverbal communication patterns can fulfill children's basic rights so that children feel comfortable, happy and protected. The concept of a child-friendly tourist village by using the provision of a play area with its facilities can increase the number of visitors. The real impact of nonverbal communication can be seen from the increase in children's sense of security, comfort, and emotional involvement while in the tourist area, which directly contributes to a positive and meaningful tourism experience. Nonverbal interaction through play tools also helps children express themselves and communicate naturally with their surroundings, supporting their learning process and social development.